Alternate Histories: Hyderabad 1948 Compels a Fresh Evaluation of the Theology of India's Independence and Partition. (July 2014) - Muralidharan, Sukumar
The past is never dead. It is not even past—William Faulkner This article reviews recent literature on the accession of the princely state of Hyderabad to the Indian union in 1948, in the context of events that have raised the temperature of communal confrontation in the region. Scholarship on nation formation has drawn attention to the role that the act of remembering only to forget, plays in cementing a sense of nationalist solidarity. By that criterion, the accession of Hyderabad presents a case of historical record that may have been abridged and in part effaced, without the consent of its more substantial minority group. This allows for historical tensions to emerge anew as fault-lines where modern democratic competition could spill over into communal antagonism. Recent efforts to restore the historical record, one by way of a memoir and the other, a work of archival scholarship, assume great importance in this regard.